1996
DOI: 10.1021/cm960113a
|View full text |Cite
|
Sign up to set email alerts
|

STM Investigations of Organic Molecules Physisorbed at the Liquid−Solid Interface

Abstract: Investigations of long-chain hydrocarbon and substituted hydrocarbon materials physisorbed at the liquid-solid interface have provided a particularly fruitful area of investigation for the scanning tunneling microscope (STM). Studies of this kind provide considerable information concerning surface-adsorbate interactions, the nature of the STM contrast mechanism for molecules adsorbed on surfaces, the effect of the chemical nature of the liquid solvent on the rearrangement and bonding of adsorbates, and the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
347
3

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 330 publications
(379 citation statements)
references
References 108 publications
29
347
3
Order By: Relevance
“…A survey of papers shows that the image of the arms is often asymmetric. 1,[15][16][17][18][19][20][21][22][23][24][25][26] Two examples from our experiments illustrate this effect in Figure 1. The alternating rows of bright and dark spots evidently correspond Image has dimensions of 7.5 nm × 7.5 nm and was recorded at a bias of -1.5 V, setpoint current of 300 pA, and a scan rate of 6.78 Hz.…”
mentioning
confidence: 70%
“…A survey of papers shows that the image of the arms is often asymmetric. 1,[15][16][17][18][19][20][21][22][23][24][25][26] Two examples from our experiments illustrate this effect in Figure 1. The alternating rows of bright and dark spots evidently correspond Image has dimensions of 7.5 nm × 7.5 nm and was recorded at a bias of -1.5 V, setpoint current of 300 pA, and a scan rate of 6.78 Hz.…”
mentioning
confidence: 70%
“…However, many subtle modifications of the self-assembled structures have been observed, depending on alkane functionalization and chain length (3, 6, 10-12, 15, 17-19, 28, 35, 36, 41, 46). Specific headgroup interactions (e.g., hydrogen bonding and electrostatic forces) (11,12,17,19,28,41) and geometric subtleties (e.g., odd vs. even chain length) (31, 32, 36) also can have a profound influence on the self-assembly. The resulting set of interactions creates competing constraints, which are evident in the calculated and measured adsorption energies (47).…”
mentioning
confidence: 99%
“…This fact allows us to assume reasonably that the adsorption occurs preferentially by the carboxylic group. Furthermore, previous STM studies on selfassembly of fatty hydroxyl acids on HPOG have shown that -COOH•••HOOC-interaction is stronger than -COOH•••HO- [17][18]. This observation may cause competition between head to head (-COOH•••HOOC-) and head to mica bonding and reverse orientation (bonded to mica through the hydroxyl group) of a fraction of molecules in the self-assembled system.…”
Section: Formation Of Multilayer Systemsmentioning
confidence: 95%